CV and CM chondrite impact melts. (15th September 2016) - Lunning, Nicole G.; Corrigan, Catherine M.; McSween, Harry Y.; Tenner, Travis J.; Kita, Noriko T.; Bodnar, Robert J.
Abstract: Volatile-rich and typically oxidized carbonaceous chondrites, such as CV and CM chondrites, potentially respond to impacts differently than do other chondritic materials. Understanding impact melting of carbonaceous chondrites has been hampered by the dearth of recognized impact melt samples. In this study we identify five carbonaceous chondrite impact melt clasts in three host meteorites: a CV3red chondrite, a CV3oxA chondrite, and a regolithic howardite. The impact melt clasts in these meteorites respectively formed from CV3red chondrite, CV3oxA chondrite, and CM chondrite protoliths. We identified these impact melt clasts and interpreted their precursors based on their texture, mineral chemistry, silicate bulk elemental composition, and in the case of the CM chondrite impact melt clast, in situ measurement of oxygen three-isotope signatures in olivine. These impact melts typically contain euhedral–subhedral olivine microphenocrysts, sometimes with relict cores, in glassy groundmasses. Based on petrography and Raman spectroscopy, four of the impact melt clasts exhibit evidence for volatile loss: these melt clasts either contain vesicles or are depleted in H2 O relative to their precursors. Volatile loss (i.e., H2 O) may have reduced the redox state of the CM chondrite impact melt clast. The clasts that formed from the more oxidized precursors (CV3oxA and CM chondrites) exhibit phase and bulk silicate elemental compositions consistent with higher intrinsic oxygen fugacities relative to the clast that formed from a more reduced precursor (CV3red chondrite). The mineral chemistries and assemblages of the CV and CM chondrite impact melt clasts identified here provide a template for recognizing carbonaceous chondrite impact melts on the surfaces of asteroids.